2013
DOI: 10.2174/1874312901307010058
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Function and Disease Activity as Measured by the HAQ and DAS28 Varies Over Time and by Rheumatoid Factor Status in Early Inflammatory Arthritis (EIA). Results from the CATCH Cohort§

Abstract: Objective:To investigate the relationship between function and disease activity in early inflammatory arthritis (EIA).Methods:Canadian Early Arthritis Cohort (CATCH) (n=1143) is a multi-site EIA cohort. Correlations between the Health Assessment Questionnaire Disability Index (HAQ) and DAS28 were done at every 3 months for the first year and then at 18 and 24 months. We also investigated the relationship between HAQ and DAS28 by age (<65 versus ≥65) and RF (positive vs negative).Results:Mean HAQ and DAS28 scor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 13 publications
2
18
0
Order By: Relevance
“…These results may suggest that joint space narrowing might not be the hallmark for joint pain in OA patients. In our previous study, the bone signal change was not seen in the cases with advanced OA without joint pain, while bone signal changes were detectable in the cases with advanced OA with joint pain [6]. In this study, signal changes were seen even in the cases without OA or with a slight degree of OA if the patients had joint pain.…”
Section: Discussionsupporting
confidence: 41%
“…These results may suggest that joint space narrowing might not be the hallmark for joint pain in OA patients. In our previous study, the bone signal change was not seen in the cases with advanced OA without joint pain, while bone signal changes were detectable in the cases with advanced OA with joint pain [6]. In this study, signal changes were seen even in the cases without OA or with a slight degree of OA if the patients had joint pain.…”
Section: Discussionsupporting
confidence: 41%
“…Disease activity, measured as swollen and tender joint counts, as well as pain, have both been shown to be associated with the total HAQ score (32). Several other studies demonstrated similar results, with associations between high disease activity and impaired PROs like HAQ (17,(33)(34)(35).…”
Section: Discussionmentioning
confidence: 77%
“…In that study, grip force and pain intensity were major contributors to disability measured using HAQ-DI (1), similar to our ndings on HAQ-DI-UE. Taken together, these studies suggest that although disability may decrease in early RA, subsequent worsening of disability is common, in particular in those with active disease and severe pain (1,33,34).…”
Section: Discussionmentioning
confidence: 81%
“…This leads to joint deformity and destruction resulting from bone and cartilage erosion, 1,2 and almost always leads to functional compromise of the structures involved. 3,4 Epidemiological studies have estimated the prevalence of RA at 1% of the adult population, ranging from 0.4 to 1.9% at world level, and from 0.5 to 1.0% in Brazil. 5,6 RA affects three times as many women as men, with the highest incidence between the ages of 30 and 50 years.…”
Section: Introductionmentioning
confidence: 99%